EVALUASI TINGKAT KEPUASAN PENGGUNA TERHADAP PROGRAM PAVINGISASI JALAN LINGKUNGAN DI KOTA MADIUN - Masyhudi, Ummi Iyyaya; Solikin, Mochamad; Mutiari, Dhani; Qomarun (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Roads are important infrastructure in supporting mobility and economic growth. Madiun City, as a developing city in East Java Province, continues to improve road infrastructure through a paving program aimed at improving accessibility and user comfort. This program has been successfully implemented in 2023 and again in 2024, covering the entire Madiun City. However, this study focused on Manguharjo sub-district with a time span from February to October 2024. This study aims to evaluate community satisfaction with neighborhood road paving using the Importance Satisfaction Analysis (ISA) and Customer Satisfaction Index (CSI) methods. In addition, this research identifies attributes that need to be improved in order to improve the quality of paving. The results show that paving quality and road safety are the main factors that need to be improved, as illustrated in Quadrant A of the ISA analysis. Meanwhile, accessibility and road width have a good level of satisfaction and need to be maintained. Based on the CSI analysis, a satisfaction index of 85% was obtained, indicating that the community as a whole was very satisfied with the results of the paving of neighborhood roads in Madiun City. Keyword: Pavingization, User Satisfaction, Importance Satisfaction Analysis (ISA), Customer Satisfaction Index (CSI), Madiun City